Two-color thermometry applied to red hot steel accompanied by water and steam. (December 2021) - Sugiura, Masato; Morioka, Kohsuke; Tsuchiya, Masaki
Abstract: Radiation thermometry plays a crucial role in temperature control in steel production. This paper proposes a new two-color radiation thermometry technique applied to obstruction problems arising from water on the high-temperature steel. The two-color thermometry requires a precise adjustment of the detection wavelengths with equal water transmissivity. Water thickness can be obtained through the attenuation of the observed radiation at the same time. A prototype two-color thermometer was designed using detection wavelengths of 1200 nm and 1300 nm. The experimental result indicates that the temperature and apparent water layer thickness of red hot steel can be measured.